Efficacy and safety of Lignosus rhinocerus (Cooke) Ryvarden TM02® supplementation for immune-challenged patients with localised breast cancer in remission: a randomised controlled trial - Jie Yi Eng; Po Lin Ooi; Mariam Zafirah; Mahmoud Danaee; Marniza Saad; Muhammad Fazril Mohamad Razif; Nor Aishah Taib; Chee Loong Lam; Zamri Chik; Shin-Yee Fung (BMC Complementary Medicine and Therapies)
Abstract Purpose of study This study aimed to evaluate the safety and effectiveness of TM02® in improving health-related quality of life (HRQoL) and fatigue in patients with localized breast cancer who had completed surgery and chemotherapy, addressing both acute and long-term side effects. Methods This phase II randomized, double-blind, placebo-controlled study evaluated the efficacy and safety of TM02® supplementation in patients who had completed surgery and chemotherapy for localized breast cancer, using HRQoL scores. A total of 52 patients were randomized into two groups: (i) TM02® (n = 26; 1,040 mg daily for 6 months) and (ii) placebo (n = 26). HRQoL scores were assessed using the EORTC-QLQC30 and QLQ-BR23 questionnaires at five time points. Fatigue scores were measured using the FACIT-Fatigue Scale, and the safety profile of TM02® was also evaluated. Data were analyzed on a per-protocol basis. Results The Global Health Status (GHS) score showed a significant within-patient effect across five visits (p = 0.001; F = 0.276). A trend toward improved physical functioning and reduced fatigue was observed in the TM02® group compared to the placebo group. TM02® was safe for consumption, with no significant differences in side effects between the two groups. Conclusions Our study found that TM02®, a natural supplement containing standardized compounds from Lignosus rhinocerus, is well tolerated in patients with localized breast cancer post-adjuvant chemotherapy. TM02® supplementation showed a positive trend towards improved physical functioning and reduced fatigue scores.